PENGGUNAAN PATI KENTANG (Solanum tuberosum) LOKAL PREGELATINASI SEBAGAI BAHAN PENGEMBANG PADA TABLET PARASETAMOL GRANUL SECARA KEMPA LANGSUNG - Agusmal Dalimunthe; Cut Masyithah Thaib; Yosy Cinthya Eriwaty Silalahi; Mira Eka Diana Br Tarigan (Jurnal Farmanesia, 2019)
Potatoes have a high nutritional content such as carbohydrates, starch, fat, protein, and water. Almost 90% of medicinal raw materials, both active substances and additives are obtained through imports and abroad, even though Indonesia's natural resources can be developed. This study aims to determine the effect of using pregelatinized local potato starch (Solanum tuberosum) as a developer in paracetamol tablets by direct compression. This research was conducted experimentally using five formulas with certain concentrations of F1 (4%), F2 (6%), F3 (8%), and F4 (10%). Then the tablet evaluation test was carried out, namely the weight uniformity test, tablet hardness test, tablet friability test, tablet disintegration time test. The results showed that the paracetamol tablets with local pregelatinized potato starch developer were made to meet the requirements for weight uniformity test, tablet hardness test, tablet friability test, and tablet disintegration time test. It can be concluded that local pregelatinized potato starch (Solanum tuberosum) can be used as a developer in paracetamol tablets.